Personal Learning Environments: Strategies and Technologies Used by Spanish University Students - Serrano-Sánchez, José Luis (2021)
Objective: This paper describes and analyzes Personal Learning Environments (PLE) of future workers in various areas of knowledge. Method. Data was collected from 2054 final-year degree students at 75 Spanish universities; the data were related to information management, learning process management, self-perception, and communication. The research had an exploratory non-experimental design, and the information was collected through a validated questionnaire. Results. The results provide a profile of students who use the Internet for information searches and communication; however, they feel more comfortable in face-to-face learning environments with teachers who clearly set defined goals rather than using the Internet for self-directed learning. Conclusions. There are limitations for using the Internet as a real working and learning space. Higher education institutions are recommended to promote programs to improve the management skills of the students’ personal learning environments for their application in the work environment.